PENENTUAN KUALITAS KULIT ULAR PADA INDUSTRI SEPATU MENGGUNAKAN METODE FUZZY SIMPLE ADDITIVE WEIGHTING (SAW) - Alhibarsyah Alhibarsyah (Industrika : Jurnal Ilmiah Teknik Industri, 2018)
Along with the emergence of competitors, shoe industry companies continue to strive to produce the best products for consumers. One effort that can be made by the company is to reduce the number of product failures by choosing the quality of raw material for shoe leather. Manufacturing companies are accustomed to improving the quality and reliability of products, and the process through preventing failure of quality shoes production is a priority of a company engaged in the leather shoes industry. The main priority for shoe industry companies is to pay attention to the raw material of shoes from snake skin, the size of snake skin, the physicality of snake skin and the color of snake skin used in the production process. In this determination the method of Fuzzy Simple Additive Weighting (SAW), which method is one method that can be used for the problem of Fu zzy Multi Attribute Decision Making (Fuzzy MADM). The Fuzyy SAW method is applied to maximize the decisions that will be taken, several supporting criteria, the weight for each criterion is also given after it is determined the normalization value from the calculation of the criteria is divided by the maximum value of each criterion and then calculated to determine the alternative ranking value to determine the skin type which snake is the best. Keywords: Quality, Snake Skin, Fuzzy Method, Simple Additive Weighting (SAW), FMADM